OP0010 Thigh Magnetic Resonance Imaging Reveals Increased Active and Chronic Muscle Damage in Necrotizing Myositis Compared To Polymyositis and Dermatomyositis. (15th July 2016) - Pinal-Fernandez, I.; Casal-Dominguez, M.; Lahouti, A.; Basharat, P.; Albayda, M.; Paik, J.; Ahlawat, S.; Danoff, S.; Lloyd, T.E.; Mammen, A.L.; Carrino, J.; Christopher-Stine, L.
Abstract : Background: The autoimmune myopathies include polymyositis (PM), dermatomyositis (DM), and necrotizing myositis (NM). Patients with clinically amyopathic dermatomyositis (CADM) have the cutaneous features of DM but with minimal or no muscle involvement. Muscle abnormalities can be assessed with magnetic resonance imaging (MRI), which detects edema (a feature of active muscle disease) and fatty replacement (a feature of chronic damage). Objectives: To compare the prevalence of active and chronic muscle damage in patients with DM, PM, NM, CADM, and IBM using thigh MRI (tMRI). Methods: All the patients of the Johns Hopkins Myositis Cohort with an available tMRI that fulfilled criteria for DM, PM, IBM, NM or CADM were included in the study. Fifteen muscles of the gluteal, lateral rotator, anterior, medial and posterior thigh compartments were studied bilaterally. In each muscle, the presence of edema, fatty replacement, and fascial thickening was recorded. We compared the tMRI features of clinical subsets using univariate and multivariate regression analysis. We also studied the effect on the tMRI, independently of the clinical subset, age at onset, sex, race and time from the onset to the tMRI. Results: Six hundred and sixty-seven patients were included in the study (153 IBM, 101 NM, 176 PM, 220 DM and 17 CADM). The prevalence of edema, atrophy, and fatty replacement showed a gradient among different clinical subsets (IBM>NM>PM>DM>CADM). Similar to patients with IBM, tMRI of NM patients revealed more frequent edema (difference >22%), atrophy (difference >27%), and fatty replacement (difference >14%) than in PM or DM. Analysis of the different muscle compartments confirmed that, as previously described, IBM is characterized by fatty replacement and atrophy in the anterior compartment; in contrast, NM was associated with atrophy and fatty replacement in the lateral rotator compartment. Fascial thickening was the hallmark of DM (found in 51%; p<0.001) while PM was not associated with any specific pattern. Independent of the clinical subset, increased age at onset was associated with more muscle atrophy (OR10 years =1.2, 95%CI 1.01–1.3), fatty replacement (OR10 years =1.4, 95%CI 1.2–1.6), and muscle edema (OR10 years =1.3, 95%CI 1.2–1.5); the time from the onset of the disease to the tMRI was only associated with fatty replacement (OR10 years =1.7, 95%CI 1.2–2.5). Conclusions: Patients with NM had more frequent edema, fatty replacement, and atrophy on tMRI compared to those with either DM or PM, suggesting that NM is often a more severe, and perhaps undertreated, form of myositis. In NM, fatty replacement occurred most frequently in the lateral rotators, whereas in IBM chronic damage was more frequent in the anterior compartment. As reported in other studies, increased fascial thickening was a hallmark feature of DM. In contrast, the lack of a consistent pattern of muscle involvement suggests that PM is a heterogeneous entity. Disclosure of Interest: None declared